1960
DOI: 10.1126/science.132.3437.1401
|View full text |Cite
|
Sign up to set email alerts
|

Callus Tissues from the Mosses Polytrichum and Atrichum

Abstract: Callus-like tissues, isolated from protonemal cultures of two species of mosses, grow vigorously and without marked differentiation on media containing sucrose, casamino acids, and coconut milk. On mineral agar and on media containing sorbitol the tissue from Polytrichum (found diploid) reverts to the growth pattern of apparently normal moss plants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

1961
1961
2000
2000

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…All of the calluses reported in Bryophytes previously by several workers have been produced from the dioecious species which are mostly diploid (Allsopp 1957, Ward 1960, Lal 1961, Rashid and Chopra 1969. In these calluses, the abnormal cells like polyploid or aneuploid have not been reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All of the calluses reported in Bryophytes previously by several workers have been produced from the dioecious species which are mostly diploid (Allsopp 1957, Ward 1960, Lal 1961, Rashid and Chopra 1969. In these calluses, the abnormal cells like polyploid or aneuploid have not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, several workers have reported that calluses of some Bryophyte species do not give any indication of polyploid or aneuploid (Ward 1960;Lal 1961;Rashid and Chopra 1969).…”
mentioning
confidence: 99%
“…Although several chlorophyllous cell lines have been derived from higher plants, the majority of the cells exhibit a low rate of photoautotrophic growth, probably because the Chi content of the cells is low. Callus cells from bryophytes generally contain a high concentration of Chi (AUsopp 1957, Ward 1960, but few attempts have been made to establish suspension cultures of bryophyte cells. However, such cultures were established from the liverworts, Marchantiapolymorpha (Katoh et al 1980), Jungermannia subulata (Ohta et al 1981) and Calypogeia granulata (Takeda and Katoh 1981).…”
Section: Introductionmentioning
confidence: 99%
“…Isoprene emitted by these early plants should be accounted for in models of early climate and biological environmental engineering. Under current climate conditions, mosses occur on every continent, dominating observed biomass in the high arctic and can tolerate a wide array of temperature and water stresses (Ward 1960;Collins 1976;Corradini et al 1999;Van der Velde et al 2001review Mishler et al 2001;Wilson et al 2003;Shafigullina et al 2018;Ojiodu et al 2018). Global warming may lead to the expansion of isoprene emitting moss communities in some regions such as Antarctica and an increase in landscape level isoprene emissions with profound implications for climate change.…”
Section: Introductionmentioning
confidence: 99%